Servo Motor Driver Design for High Performance Applications - Yasa, Yusuf; Sahin, Ergin; Acar, Cilem; Gozutok, Aybuke; Firat, Ecem; Mese, Erkan (IEEE, 2013)
The motion control applications have become quite common in recent years. This makes the design and control of the motor very popular. Especially in high performance applications, permanent magnet synchronous motors, which are often called servo motor, are used nowadays. In this paper, the process of high performance motor driver design will be presented. These stages are; main power circuit, supply circuit, fault protection circuit, ADC (Anolog Digital Converter) signal conditioning circuit, CAN (Controller Area Network) communication circuit, Mosfet drive circuit and microcontroller. To make maximum use of real estate in the driver, components and PCB card placements are optimized. The driver is supplied by battery as DC source and its energy management is important as an enabler of longer battery life. A solution is presented for a reasonable battery energy management. Some thermal analysis and subsequent design procedure is given for power switch heat sink. Simulations are performed at both circuit and system levels before the experimental prototype have been built. Validation of the driver prototype has been performed with a PMSM motor and the results are quite promising before transition starts into the production stage.
Keywords: control of permanent magnet synchronous motor; electric motor driver design; servo applications; Energy & Fuels; Engineering